Monitoring Lung Injury Severity and Ventilation Intensity during Mechanical Ventilation - Rezoagli, Emanuele; Laffey, John G.; Bellani, Giacomo (Seminars in Respiratory and Critical Care Medicine, 2022)
Acute respiratory distress syndrome (ARDS) is a severe form of respiratory failure burden by high hospital mortality. No specific pharmacologic treatment is currently available and its ventilatory management is a key strategy to allow reparative and regenerative lung tissue processes. Unfortunately, a poor management of mechanical ventilation can induce ventilation induced lung injury (VILI) caused by physical and biological forces which are at play. Different parameters have been described over the years to assess lung injury severity and facilitate optimization of mechanical ventilation. Indices of lung injury severity include variables related to gas exchange abnormalities, ventilatory setting and respiratory mechanics, ventilation intensity, and the presence of lung hyperinflation versus derecruitment. Recently, specific indexes have been proposed to quantify the stress and the strain released over time using more comprehensive algorithms of calculation such as the mechanical power, and the interaction between driving pressure (DP) and respiratory rate (RR) in the novel DP multiplied by four plus RR [(4 × DP) + RR] index. These new parameters introduce the concept of ventilation intensity as contributing factor of VILI. Ventilation intensity should be taken into account to optimize protective mechanical ventilation strategies, with the aim to reduce intensity to the lowest level required to maintain gas exchange to reduce the potential for VILI. This is further gaining relevance in the current era of phenotyping and enrichment strategies in ARDS.
Keywords: lung injury; mechanical ventilation; gas exchange; respiratory mechanics; ventilation intensity